Hand Dexterity and Its Effect on Acquiring Basic Suturing Skills among Pre-clinical Medical Students - Pranjal Shah; Brinnell Caszo; Gnanajothy Ponnudurai; Mohammad Arshad Ikram; Siddharth Dhanaraj; Justin Gnanou (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Hand dexterity is essential for executing fine motor tasks, especially in surgical procedures such as suturing. Comprehending the significance of hand dexterity in suturing is essential for enhancing surgical training and expertise. Thus, this study aimed to examine hand dexterity on suturing skills among pre-clinical students. Material and Methods: A prospective study design was used and was conducted on twenty male undergraduate medical students with no prior surgical suturing experience. The Purdue Pegboard test was used to assess hand dexterity. This was followed by assessing basic suturing skills, which involved assessment of participants' suturing skills on two types of sutures (simple interrupted and simple continuous) by independent raters using a standardized rubric and time metrics. Pearson regression analysis was used to assess the dexterity-suturing relationships. Results: The study results indicated no association between hand dexterity and suture time for simple interrupted suture (r=0.085), while a weak negative association was observed for hand dexterity and suture time for simple continuous suture (r=0.303), suggesting individuals with a high dexterity score tool less time to complete the suture. Overall surgical assessment score showed a weak positive correlation between hand dexterity and suturing skill (r=0.308). However, no statistical significance was achieved for the correlations (p=0.05).. Conclusion: Our study findings highlight a weak association between hand dexterity and suturing performance, which depends on the duration and complexity of the task. This finding could be used to develop structured training among undergraduate medical students in developing suturing skills.